The Impact of Obstetric Care Education on Prenatal Health Behaviors among Pregnant Women - Fadlan Ramadhan; Anin Anindita (Generasi Sains Indonesia, 2025)
This study investigates the effect of obstetric care education on prenatal health behaviors among pregnant women, using a quantitative research design to provide empirical evidence on its effectiveness. Maternal health remains a critical global issue, particularly in low- and middle-income countries, where educational interventions are increasingly recognized as cost-effective means to promote healthy prenatal practices. Data were collected from surveys administered to pregnant women who participated in obstetric education programs, and both descriptive and inferential statistical analyses were conducted to assess the impact of education on behavioral changes. The results revealed significant improvements in key prenatal health behaviors, such as regular antenatal clinic visits, adherence to nutritional guidelines, physical preparedness, and avoidance of harmful practices. These findings highlight the importance of obstetric care education as an essential management intervention in maternal healthcare systems. The study demonstrates that integrating education into routine antenatal care can serve as both a preventive strategy and a tool for improving service delivery and reducing risks. It also emphasizes the need for healthcare managers, policymakers, and practitioners to institutionalize educational programs, ensuring their integration into standard maternal health services to promote equity and sustainability in maternal health outcomes.